2015
DOI: 10.1186/s12969-015-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary complement and antibody deficiencies in autoimmune rheumatologic diseases with juvenile onset: a prospective study at two centers

Abstract: BackgroundOur aim was to investigate the prevalence and clinical relevance of inherited complement and antibody deficiency states in a large series of patients with various autoimmune rheumatologic diseases (ARD) with juvenile onset.MethodsA total number of 117 consecutive patients from 2 tertiary referral hospitals were included in the study. All patients underwent genetic screening for type I C2 deficiency and C4 allotyping. Serum levels of immunoglobulin classes measured systematically throughout their regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Earlier studies have found an association between JIA and IgA deficiency (11,17), but the prevalence of IgA deficiency in JIA is unclear. The study by Ludvigsson et al (11) was a retrospective study on children with IgA deficiency, and the study by Sparchez et al (17) only included 84 children with JIA. In the present study, the prevalence of selective IgA deficiency was 0.95% (2/211).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Earlier studies have found an association between JIA and IgA deficiency (11,17), but the prevalence of IgA deficiency in JIA is unclear. The study by Ludvigsson et al (11) was a retrospective study on children with IgA deficiency, and the study by Sparchez et al (17) only included 84 children with JIA. In the present study, the prevalence of selective IgA deficiency was 0.95% (2/211).…”
Section: Discussionmentioning
confidence: 95%
“… was a retrospective study on children with IgA deficiency, and the study by Sparchez et al. only included 84 children with JIA. In the present study, the prevalence of selective IgA deficiency was 0.95% (2/211).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To note, family members that carry the same gene mutation may present different types of autoimmune/autoinflammatory symptoms, or without such disorders [22]. In comparison with other types of defects, the autoimmune presentations are relatively common in PIDs with antibody deficiencies (e.g., CVID, selective IgA deficiency), and absence of initial components (C1-C4) of the classical complement system [23,24].…”
Section: Autoimmune and Autoinflammatory Disordersmentioning
confidence: 99%
“…Also, inflammatory markers, complete blood count, liver function tests, antinuclear antibody testing, rheumatoid factor or anti-cyclic citrullinated peptide antibody could be useful. [37,38] …”
Section: Manifestationmentioning
confidence: 99%